Intersectionality between young people, environmental disasters and the criminal justice system in Australia - Jokovic-Wroe, Deni; Collingburn, Leanne; Reidy, Nell; Williamson, Bhiamie (Frontiers in Human Dynamics, 2025)
There is an absence of research specifically addressing the intersectionality between young people, environmental disasters and the criminal justice system globally. This paper examines the existing literature for the likely connections between young people impacted by environmental disasters in Australia, with a particular focus on young Indigenous people, and their future intersection with the criminal justice system. Young people and Indigenous communities are particularly vulnerable to the detrimental effects of environmental disasters. In analyzing the similarities between those unique vulnerabilities and the common risk factors for engagement in the criminal justice system, we infer that exposure to environmental disasters can increase the likelihood of young people, particularly young Indigenous people, engaging in the criminal justice system in Australia. Empirical research on this topic is paramount to developing measures for preventing and reducing engagement in the criminal justice system for young people impacted by environmental disasters. Ultimately, young people exposed to environmental disasters may be at increased risk of future exposure to the criminal justice system.